Historic First: Testimony of a Foresight / Corporate Communications & International Relations Office, UiTM - UiTM, Corporate Communications & International Relations Office (Corporate Communications & International Relations Office, UiTM, 2006)
Universiti Teknologi MARA was conceived in 1956 on the foundation that training would rebuild the rural society, thus improving its economy. In its early days of development as the Rural and Industrial Development Authority (RIDA) Training Centre, professional courses offered were intended to equip rural individuals with skills that would allow them to maximise their potentials thus uplifting their economic status. The centre conducted the examination for a professional course under the London Chamber of Commerce, UK. This was followed by examinations under the Australia Society of Accountants, the Corporation of Secretaries, UK, the British Institute of Management, Chartered Institute of Secretaries, LL.B. London and a few others.